Cover Image, Volume 23, Issue 8. Issue 8 (16th July 2021) - Gong, Jessica; Harris, Katie; Hackett, Maree; Peters, Sanne A. E.; Brodaty, Henry; Cooper, Mark; Hamet, Pavel; Harrap, Stephen; Mancia, Giuseppe; MacMahon, Stephen; Chalmers, John; Woodward, Mark
Abstract : The cover image is based on the Original Article Sex differences in risk factors for cognitive decline and dementia, including death as a competing risk, in individuals with diabetes: Results from the ADVANCE trial by Jessica Gong et al., https://doi.org/10.1111/dom.14391 .